Role of meiobenthic assemblages in detritus based food chain from estuarine environment of Goa - Kulkarni, Shantanu S; Rivonker, C U; Sangodkar, U M X (Indian Journal of Fisheries, 2011)
The paper describes the variations in ecological parameters and their possible role on vertical distribution of meiobenthic communities in the estuarine marshy environment at Goa. The investigations conducted during post monsoon season suggest that hydrobiological parameters are regulated by local attributes such as land use pattern and coastal processes. Further, the variation in environmental characteristics had direct relationship with meiobenthic population density and its variations. Among biological parameters the sediment Chlorophyll a (Chl a) was found to be closely related with meiobenthic density (r= 0.89: p<0.001). The fauna showed higher concentration at 0-2 cms layer. Subsequently, as the depth increased, there was significant decrease in the density of meiobenthic organisms. Another conspicuous observation made in the present study was abundant supply of organic carbon up to a depth of 5 cm.